Survey of maedi-visna (MV) in Ethiopian highland sheep - Ayelet, G.; Roger, F.; Tibbo, Markos; Tembely, S. (Elsevier, 2001)
A serological survey was carried out in the central highlands of Ethiopia to investigate the significance of maedi-visna on sheep reared in two types of management, on-station and on-farm. A total of 349 serum samples were collected in January 1996 from ILRI Debre Berhan station (n=203) and adjacent farms (n=146), and Agar Gel Immunodiffusion (AGID) test was used to determine the presence of specific maedi-visna virus antibody. An additional 1104 cases of pneumopathies have been recorded including respiratory symptoms. Post mortem data recorded at the ILRI station revealed a breed difference in terms of sensibility: 10.5% for Horro (63/603 animals) and 21.6% for Menz (108/501 animals), P<0.001. The mean ages of affected Horro and Menz were 20±1.3 and 30±1.9 months, respectively and 27±1.7 months, overall. Clinical signs recorded for suspicion of interstitial pneumonia were dyspnoea accounting for 57%, coughing for 55% and nasal discharge for 6.4%. The duration of clinical signs for interstitial pneumonia was 35.3 days vs. 16.4 for other causes. In the present study, a prevalence rate of 3.7% was obtained out of 349 sheep sera examined for the presence of MV virus surface glycoprotein (gp135) specific antibodies. There was a significant difference between samples collected from the farms and the station (P<0.05). The prevalence rate was higher (P<0.05) in males sheep than females (10.0% and 2.9% respectively). A peak of seropositivity was observed at the age of 36 months. A breed comparison between the Menz and the Horro on-station showed little difference with a prevalence rate of 5.9% and 4.8% respectively. The danger of intensification of breeding in the tropics is stressed.